The Paleocene-Eocene Thermal Maximum as recorded by Tethyan planktonic foraminifera in the Forada section (northern Italy) - LUCIANI V; GIUSBERTI, LUCA; AGNINI, CLAUDIA; BACKMAN J; FORNACIARI, ELIANA; RIO, DOMENICO (Marine Micropaleontology, 2007)
The Forada section in the Venetian Pre-Alps of northern Italy represents an expanded record of the Paleocene–Eocene Thermal Maximum (PETM) at a depositional paleodepth of about 1 km±0.5 km. High-resolution planktonic foraminiferal analysis of this section, in a time interval of approximately 1.3 Myr across the Paleocene/Eocene boundary, reveals striking faunal changes that allow the identification of eight phases (a–h). The late Paleocene was represented by stable, warm and oligotrophic surface water conditions (phase a). Unstable environmental conditions start well before the onset of PETM (ca. 150 kyr, phase b) and involved a change towards eutrophy, as marked by the increase of Subbotina and the concomitant decrease of Morozovella. This step is also characterized by enhanced fragmentation and dissolution. The interval corresponding to the main body of the carbon isotope excursion (CIE) is characterized by a marked increase of Acarinina, though with some differences in the species composition and relative abundance, both in high-and low-latitudes, particularly in the Tethyan area. Forada is no exception to this pattern. However, at Forada, two prominent peaks in abundance of acarininids are recorded ca. 30 kyr prior to the onset of the CIE, thus suggesting an increase in temperature heralding the onset of the PETM (phase c). Interestingly, the lower peak in abundance of Acarinina just precedes the 1‰ carbon isotope negative shift occurring below the onset of the main CIE. The basalmost Eocene, corresponding to the lower part of CIE curve, is represented by intense planktonic foraminiferal dissolution, implying an extraordinary rise of the CCD. This interval has an estimated duration of about 16 kyr (phase d). The dominance of acarininids in the lower part of the CIE (phase e, f; ca. 14 and 22.5 kyr) is interpreted as a consequence of the extreme warmth coupled with eutrophic conditions characterizing the Forada depositional environment at that time. These acarininids include at Forada also the temporally ...